Bitch : on the female of the species - Cooke, Lucy, 1970- (Basic Books, 2022)
A leading zoologist takes a fierce and often humorous look at the females of the animal kingdom and subverts the prevailing opinion among evolutionary biologists who have insisted that males are more interesting.